Desafios estratégicos dos hospitais filantrópicos sediados em Porto Alegre - Pinheiro, Reimbran Kolling (Universidade do Vale do Rio dos Sinos, 2013)
This study aims to identify which are the main strategic challenges of philanthropic hospitals based in Porto Alegre, Rio Grande do Sul, in the perspective of its senior managers and industry experts. The survey also included the identification of strengths, weakness, opportunities and threats, and trends in the segment. Therefore, we conducted a literature review on the health market, strategy and health management. We used a qualitative methodology of multiple case studies, in order to get the perspective of managers and specialists. We interviewed four hospital managers and two industry experts. The results reveal the existence of several strategic challenges, among which we highlight the need for improvement in the quality medical care, to ensure the safety of patients, overcoming the mismatch between revenues and hospital costs and the need for increased installed capacity of hospitals, so that they are able to satisfactorily meet the demand for their services. The study also reveals an environment full of peculiarities and opportunities.
Keywords: Estratégia; Desafios estratégicos; Hospitais filantrópicos; Gestão em saúde; Strategy; Strategic challenges; Philanthropic hospitals; Health management; ACCNPQ::Ciências Sociais Aplicadas::Administração